The effectiveness of a new domestic carbohydrate-protein product in the practice of training of high class - Vdovenko, N. V.; Ivanova, A. M.; Khrobatenko, O. V.; Rossokha, G. V.; Kostyuchenko, V. I. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The effect of the use of the new course of the carbohydrate-protein product on the performance efficiency of skilled athletes (Greco-Roman). In the experiment involved 14 athletes aged 18-25 years who gave written consent to participate in the study. Developed and clinically tested a specialized carbohydrate-protein food product. The drink contains in its composition: glucose, sucrose, whey protein concentrate, creatine monohydrate, citrulline malate, mineral complex and ATP-lipid complex. The study was conducted in two micro-cycles (2 weeks). Athletes take a drink as follows: pre-workout (30-40 minutes) - 250 ml of the drink, after a training session during the recovery period - 250 ml of the drink. It is established that the use of the drink has a positive effect on the performance of athletes performance during the execution of a sub-maximal anaerobic power in the area of energy supply. Argues that course application beverage reduces the severity of manifestations of lactate acidosis after exercise by improving the utilization of lactate. Found a significant decrease in the concentration of lactate in the blood of athletes in the 7th minute of recovery in relation to the original data.